2017
DOI: 10.1186/s12889-017-4162-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between symptoms of mental disorders and health risk behaviours in Vietnamese HIV positive outpatients: a cross-sectional study

Abstract: Background: A high prevalence of symptoms of mental disorders (SOMD) has been found among people living with HIV/AIDS (PLHIV). Additionally, SOMD may impact on the prevalence of high-risk health behaviours (HRB). This study investigates the relationship between SOMD and HRB in a large sample of Vietnamese HIV positive outpatients. Methods: A cross-sectional study was conducted with 400 outpatients at two HIV/AIDS clinics in Ho Chi Minh City, Vietnam, selected using a systematic sampling technique. Validated sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 58 publications
1
7
0
9
Order By: Relevance
“…This estimate is consistent with previous reports on depression prevalence among people living with HIV of 40–42% worldwide [ 34 ]. Prior studies measuring prevalence in Vietnam found a range from 19% to 40% of people living with HIV reported current depressive symptoms [ 24 – 28 , 47 ]. The elevated prevalence of severe depressive symptoms in our study among HIV-positive PWID, compared to prior work that did not focus on PWID, supports our hypothesis that PWID are particularly vulnerable to depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This estimate is consistent with previous reports on depression prevalence among people living with HIV of 40–42% worldwide [ 34 ]. Prior studies measuring prevalence in Vietnam found a range from 19% to 40% of people living with HIV reported current depressive symptoms [ 24 – 28 , 47 ]. The elevated prevalence of severe depressive symptoms in our study among HIV-positive PWID, compared to prior work that did not focus on PWID, supports our hypothesis that PWID are particularly vulnerable to depression.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in more comparable settings in Indonesia and China focused on PWID not known to be HIV-positive [ 8 ] or enrolled participants who were engaged in HIV care and no longer active drug users [ 9 ]. To date, studies in Vietnam have assessed the prevalence of depressive symptoms in HIV-positive populations, with estimates ranging from 19% to 40% [ 24 – 28 ]. However, none of these studies has focused on HIV-positive PWID, and the prevalence in this high risk group remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A study among 1016 PWH in Vietnam found that 30.1% of PWH had hazardous alcohol use [46]. Vietnamese PWH are also commonly affected by mental health disorders such as depression and anxiety [47,48]. Using data from a randomized controlled trial of two alcohol reduction interventions among PWH with hazardous alcohol use in Vietnam, we aim to [1] evaluate the longitudinal association between mental health symptoms (depression and anxiety symptoms) and two HIV outcomes (VS and complete ART adherence) among ART clients with hazardous alcohol use in Vietnam; and [2] determine whether alcohol dependence modifies the longitudinal association between depression, anxiety symptoms and HIV outcomes (conceptual model shown in Figure S1).…”
mentioning
confidence: 99%
“…Las personas que viven con el virus del sida (PVVS) que son conscientes de su estado seropositivo pueden seguir participando en comportamientos de salud de alto riesgo (HRB, por sus siglas en inglĂ©s), las prĂĄcticas sexuales inseguras (PSU) y el uso de drogas intravenosas entre las PVVIH representan importantes fuentes de transmisiĂłn de enfermedades secundarias (12) .…”
Section: Discussionunclassified
“…En la actualidad se habla de una pandemia de VIH alrededor del mundo siendo uno de los principales medios de transmisiĂłn las prĂĄcticas sexuales inadecuadas, donde la poblaciĂłn de riesgo en aumento son los menores de 25 años, que por lo general es la universitaria (11,12) .…”
Section: Discussionunclassified